Zaakwarneming: Legal Balance for Gestor and Dominus - Panjaitan, Wijaya Natalia (TATOHI: Jurnal Ilmu Hukum, 2025)
Introduction: Zaakwarneming refers to the voluntary managing of another person's matters without a formal agreement, namely the gestor acting in the interest of the dominus. This research discusses how the zaakwarneming principle creates a balance between the dominus and the gestor by utilizing the authority granted in Article 1354 of the Civil Code. It analyzes the application of this principle in various legal situations and assesses its impact on the responsibilities and rights of both parties.Purposes of the Research: The purpose of this study is to analyze the legal Balance for gestor and dominus in zaakwarneming.Methods of the Research: The type of research used is Normative Juridical with the type of library research.Findings of the Research: The analysis results show that the regulation of zaakwarneming should provide a fair and effective legal basis and provide a balanced arrangement for the gestor and dominus.